IMMUNO-INFLAMATORY RESPONSE IN ISCHEMIC HEART DISEASE - N. E. Zakirova; N. Kh. Khafizova; I. M. Karamova; A. N. Zakirova; R. G. Oganov (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To estimate the role of immuno-inflammatory response in developing of angina pectoris in patients with ischemic heart disease (IHD).Material and methods: The study included 83 patients with IHD and angina pectoris of functional class (FC) II (30 patients), III (27 patients) and IV (26 patients). The control group included 25 healthy persons. Bicycle burden test, daily ECG monitoring and echocardiography were used to verify of IHD. Levels of С-reactive protein (CRP), pro-inflammatory cytokines: interleukin-1β, interleukin-6 (IL-1β, IL-6) and tumor necrosis factor alpha (TNF-α) were examined by immunoenzyme method. Levels of anti-inflammatory cytokines were also defined: interleukin-4 and interleukin-10 (IL-4, IL-10).Results. Increased levels of IL-4 and IL-10 with normal CRP and pro-inflammatory cytokine levels were observed in patients with angina of FC-II. Angina of FC-III was associated with a moderate increase in CRP level and normal levels of IL-4 and IL-10. The maximal levels of CRP and pro-inflammatory cytokines as well as minimal levels of anti-inflammatory cytokines were observed in patients with FC-IV angina pectoris.Conclusion. The immuno-inflammatory response depends on angina pectoris severity in patients with IHD. Severe angina pectoris is accompanied by raised expression of pro-inflammatory cytokines and deficiency of anti-inflammatory cytokines.